Complex Neurochemical Microstructure of the Stria Terminalis in Infant and Adult Macaque Monkey - Sakharkar, Mitali; Rockland, Kathleen S.; Duque, Alvaro (Frontiers in Neuroanatomy, 2022)
The stria terminalis (ST) is a major bidirectional fiber tract anchored in the amygdala and bed nucleus (BNST). Extensive investigations in rodents report a complex arrangement of neurochemically diverse neurons within the ST, but fewer data are available for non-human primates. Given the functional importance of the ST, we investigated its microarchitecture in one newborn, four infant, and two adult macaque brains, by parallel immunocytochemical series for cells or fibers. Main results are as follows: (1) The pan-neuronal marker NeuN shows scattered neurons and small neuronal clusters in both the dorsal and ventral ST, but more numerous dorsally; (2) smaller neuronal subpopulations are labeled by calretinin (CR), neuropeptide Y (NPY), calbindin (CB), and somatostatin (SOM), of which the CR + neurons are the most numerous; (3) the infant brains on average have more neurons in the ST than the adult brains, but across our sample, there is notable individual variability; and (4) fiber architectonics have a complex organization, which can be referenced to myelin-poor or myelin-dense zones. Myelin-poor zones coincide with concentrations of fibers positive for CB, CR, or tyrosine hydroxylase (TH). Neurons have been reported in other white matter domains (e.g., anterior commissure, corpus callosum, cingulum bundle, and subcortical white matter). Like these, at least some neurons within the ST may give rise to long-distance connections, and/or participate in more local functions, such as vascular regulation or axon guidance/maintenance.